2014
DOI: 10.1111/den.12277
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic diagnosis of superficial non‐ampullary duodenal epithelial tumors in Japan: Multicenter case series

Abstract: Background and Aim:To verify the current status in Japan on endoscopic diagnosis of superficial non-ampullary duodenal epithelial tumors (SNADET) by a multicenter case series through a questionnaire survey.Methods: Nine endoscopists and a surgeon responded to a questionnaire on endoscopic diagnosis of SNADET. The subjects of this survey were histologically confirmed SNADET that were endoscopically or surgically resected from 2007 to 2012. This survey collected data of 364 patients with 396 SNADET.Results: Of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
230
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(256 citation statements)
references
References 27 publications
(47 reference statements)
12
230
4
Order By: Relevance
“…Unfortunately, they often achieve fewer en bloc resections. Because the malignant potential of NASDTs is extremely difficult to define from the macroscopic preoperative diagnosis [10,11], in clinical practice now, the most reliable conclusive diagnosis is the total excisional biopsy using EMR or ESD. However, there were no precise detailed criteria for the selection of EMR and ESD according to the size or the location of the lesion.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, they often achieve fewer en bloc resections. Because the malignant potential of NASDTs is extremely difficult to define from the macroscopic preoperative diagnosis [10,11], in clinical practice now, the most reliable conclusive diagnosis is the total excisional biopsy using EMR or ESD. However, there were no precise detailed criteria for the selection of EMR and ESD according to the size or the location of the lesion.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of duodenal adenomas was reported to be <0.4% in subjects who underwent esophagogastroduodenoscopy [2]. However, recently it has been reported that the incidence of duodenal carcinoma has been increasing during the past 2 or 3 decades [3], presumably due to the widespread application of upper endoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the results of this study are useful for the identification of benign and malignant lesions in SNADTs (10). Furthermore, a multicenter study revealed that a significantly higher number of high-grade dysplasia or superficial adenocarcinomas compared with low-grade dysplasia were identified in tumors with a diameter >5 mm with solely or predominantly red coloration (9). According to the aforementioned categorical descriptions, the lesion in the present study was identified to possess a mixed type surface with an unclassified pattern vessel and may be a category 4/5 tumor.…”
Section: Discussionmentioning
confidence: 70%
“…However, owing to the limited number of SNADT cases, the additional advantages of magnifying endoscopy in early duodenal cancer remain unknown and additional studies are required. Furthermore, due to the thin wall of the bowel, unintended fibrosis induced by common biopsy may affect subsequent ER, and the diagnostic accuracy of enhanced endoscopy and biopsy has been identified to be similar (78 and 75%, respectively) (9,25). Therefore, in the present case report, the ESD procedure was performed to remove the lesion for pathological analysis instead of forcep biopsy.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation